2016
DOI: 10.1080/00016489.2016.1247497
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic rhinosinusitis on long-term survival in lung transplantation recipients

Abstract: One hundred and forty-eight patients received lung transplantation for various indications. Chronic rhinosinusitis was found in 18.9% (28/148) of the lung transplantation recipients. Of 28 patients with chronic rhinosinusitis, seven patients underwent endoscopic sinus surgery due to persistent post-nasal drip. The recipients with chronic rhinosinusitis who did not receive endoscopic sinus surgery (n = 21) showed a significantly lower survival rate as compared to the patients without chronic rhinosinusitis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…11,12,25 In light of the excellent outcomes observed in these patients, a surgically oriented approach may be advocated earlier in the management course of these patients. This is further supported by a recent study 26 that compared survival rates among lung transplant recipient patients with CRS who underwent ESS with those who were managed conservatively. In that study, ESS correlated with increased survival rates.…”
Section: Chronic Rsmentioning
confidence: 61%
“…11,12,25 In light of the excellent outcomes observed in these patients, a surgically oriented approach may be advocated earlier in the management course of these patients. This is further supported by a recent study 26 that compared survival rates among lung transplant recipient patients with CRS who underwent ESS with those who were managed conservatively. In that study, ESS correlated with increased survival rates.…”
Section: Chronic Rsmentioning
confidence: 61%
“…13 Looking at other solid organ transplant recipients, a lower mortality was found in lung transplant recipients with sinusitis who underwent FESS prior to transplantation compared to those who did not, while the presence of abnormalities on sinus CT was not associated with mortality. 20 In contrast, the prevalence of sinusitis was not increased in a large cohort of kidney transplant recipients, nor did asymptomatic patients show any deterioration of clinical course after transplantation. 21 Literature on the decision to treat sinusitis before solid organ transplantation is thus somewhat conflicting.…”
Section: Subgroupmentioning
confidence: 86%
“…A large Korean study in liver transplant recipients confirmed the absence of complicated infections but found better survival in sinusitis patients who were adequately treated before transplantation 13 . Looking at other solid organ transplant recipients, a lower mortality was found in lung transplant recipients with sinusitis who underwent FESS prior to transplantation compared to those who did not, while the presence of abnormalities on sinus CT was not associated with mortality 20 . In contrast, the prevalence of sinusitis was not increased in a large cohort of kidney transplant recipients, nor did asymptomatic patients show any deterioration of clinical course after transplantation 21 .…”
Section: Discussionmentioning
confidence: 98%
“…La rinosinusitis crónica es frecuente en pacientes con indicación de trasplante pulmonar, especialmente en aquellos pacientes con fibrosis quística (FQ), siendo más de la mitad de ellos sometidos a CEF previo al trasplante 14 . Esta asociación se ha explicado en base al concepto de vía aérea unificada y a que la descarga posterior puede inducir a la infección respiratoria baja, convirtiéndose en una fuente de infección durante la inmunosupresión postrasplante 15 . Distintos estudios demuestran que el tratamiento de la rinosinusitis tiene un efecto positivo en la prevención de infecciones postrasplante [16][17][18] , además se ha reportado que el drenaje crónico con patógenos en aloinjertos pulmonares es causado por el reservorio bacteriano de los senos paranasales 19 , siendo incluso genotípicamente idénticos 20 .…”
Section: Consideraciones En Pacientes Con Trasplante Pulmonarunclassified
“…En 148 pacientes que recibieron trasplante pulmonar debido a diversas indicaciones, aquellos receptores que presentaban RSC previa al trasplante y que no recibieron cirugía endoscó- pica funcional el porcentaje de sobrevida global fue significativamente menor que aquellos que sí fueron sometidos a CEF, en estos últimos la curva de sobrevida se compara a la de los pacientes sin RSC con un seguimiento mayor a 12 años. En este mismo estudio no existieron diferencias significativas en las curvas de sobrevida al analizar aquellos receptores con y sin anormalidades imagenológicas en la TC 15 .…”
Section: Consideraciones En Pacientes Con Trasplante Pulmonarunclassified